Kinetic features of carbonyl reductase 1 acting on glutathionylated aldehydes. (1st October 2017) - Moschini, Roberta; Rotondo, Rossella; Renzone, Giovanni; Balestri, Francesco; Cappiello, Mario; Scaloni, Andrea; Mura, Umberto; Del-Corso, Antonella
Abstract: The attempt to evaluate the human carbonyl reductase 1 (CBR1) activity on 3-glutathionylated-4-hydroxyalkanals through the classical spectrophotometric assay, in which NADPH oxidation is monitored at 340 nm, failed. This was due to the ability of the enzyme to catalyze the reduction of the free aldehyde form and at the same time the oxidation of the hemiacetal structure of this class of substrates, thus leading to the occurrence of a disproportion reaction sustained by a redox recycle of the pyridine cofactor. Making use of glutathionylated alkanals devoid of the 4 hydroxyl group, and thus unable to structurally arrange into a cyclic hemiacetal form, the susceptibility to inhibition of CBR1 to polyphenols was tested. Flavones, that were much more effective than isoflavones, resulted able to modulate the reductase activity of the enzyme on this new peculiar class of substrates. Highlights: Flavones inhibit carbonyl reductase 1 (CBR1) catalyzed reduction of glutathionylated aldehydes. The inhibition of CBR1 by flavones may contribute to their anti-inflammatory action. The reduction of 3-glutathionyl-4-hydroxyalkanals by CBR1 cannot be revealed by spectrophotometric assay.